Mempertahankan Efektivitas Belajar di Tengah Pandemi melalui Penguatan Keterampilan Literasi - Imas Maesaroh (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2020)
Learning in the digital era requires digital literacy skills. This article aims to discuss the concept of literacy and the use of digital literacy in supporting the learning of students and students in the online learning era. Through literature review, this study collected data from available secondary sources, including journal articles, books, and website sources that were trusted for publication. This study found that the concept of literacy has undergone a metamorphosis from the simple ones, namely the ability to read, write, and do arithmetic, into information, media, and technology literacy skills. Literacy capabilities have an impact on the development of new knowledge and creativity in the fields of technology, education, work, and industry. Cumulative literacy skills are needed for online learning to remain effective, including listening, speaking, reading, and writing, which is supported by information, digital, and technology literacy skills